Serious game for first aid - Ain Nur Najwa, Abdul Wahab (2018)
Basic first aid is a must know knowledge that has to be integrate into every human being. Basic first aid can helps those in an emergency and prevent small injuries from becoming big and big injuries from becoming worse. The skill can make a different in saving people life. In order to master this first aid skill, a good basic of what is first aid and what to know first is important. Thus, this thesis is focusing on the development of serious game application for basic first aid in order to help general public learning basic first aid in the most fun way. The game is develops using Unity software. This module implements fun approaches for serious game application where player can choose between two game mode which are tutorial and task. Tutorial mode is the module that allows player to be guide to develop new skills. Task mode is the module that allows player to test new skills within a time constraint. The game application applies repetitive mode that will allow player to memorize the skills better.